A multicenter, open-label study of the efficacy and safety of telmisartan in mild to moderate hypertensive patients - Plavnik,Frida Liane (2002)
OBJECTIVE: To evaluate the efficacy and tolerability of telmisartan, given once a day to patients with mild to moderate hypertension, as well as to assess the 24-hour blood pressure profile with ABPM. METHODS: Initially, 163 patients over 18 were selected, regardless of sex, with blood pressure levels >140/90mmHg at visit 1, which was confirmed at visit 2. One hundred thirty-four patients completed the study. After a 4-week placebo run-in phase, telmisartan 40mg/daily was given for 6 weeks. In those patients whose blood pressure (BP) levels were lower than 140/90mmHg, the same dosage was kept for an additional period of 6 weeks. For those who had BP higher than 140/90mmHg, the dosage was increased to 80mg/daily. Sixty-two patients were included in a subgroup that underwent ABPM 3 different times during the study. RESULTS: In the overall group, blood pressure reduction ranged from 162.3±14.5/101.3±5.75 mmHg (baseline) to 147.3±20.1/90.8±10.9 mmHg (week 12) (p<0.05). Mean blood pressure decreases were 14.4mmHg for systolic BP and 10.3mmHg for diastolic BP, after 12 weeks of active treatment. A subanalysis showed that 47 (35%) patients took telmisartan 40mg throughout the study and 81 (65%) had the dosage increased to 80mg daily. Using ABPM, an 8-mmHg reduction in systolic BP as well as a 5-mmHg reduction in diastolic BP were observed, when compared with baseline values in the final 6 hours (18-24 hours after the last dose of study medication). CONCLUSION: Our results confirm that telmisartan given once a day is effective in reducing blood pressure levels in mild to moderate hypertensive patients. This reduction occurs in a sustained and gradual manner during a 24-hour period confirmed by ABPM.